2016
DOI: 10.1080/15476286.2016.1259784
|View full text |Cite
|
Sign up to set email alerts
|

Toxins MazF and MqsR cleave Escherichia coli rRNA precursors at multiple sites

Abstract: The endoribonuclease toxins of the E. coli toxin-antitoxin systems arrest bacterial growth and protein synthesis by targeting cellular mRNAs. As an exception, E. coli MazF was reported to cleave also 16S rRNA at a single site and separate an anti-Shine-Dalgarno sequence-containing RNA fragment from the ribosome. We noticed extensive rRNA fragmentation in response to induction of the toxins MazF and MqsR, which suggested that these toxins can cleave rRNA at multiple sites. We adapted differential RNA-sequencing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
34
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 69 publications
(109 reference statements)
6
34
0
Order By: Relevance
“…However, these particular 16S rRNA bases are paired in the 30S subunits, making the MazF-dependent cleavage very unlikely. It was later shown that indeed, MazF cleaves the rRNAs in their precursor states, before the 30S subunit biogenesis, and at multiple sites (Mets et al, 2017;Culviner and Laub, 2018). This is in agreement with structural data showing that MazF binds to single-stranded RNA (ssRNA) and interacts with the bases (Simanshu et al, 2013;Zorzini et al, 2016).…”
Section: Mazf Toxinssupporting
confidence: 77%
See 2 more Smart Citations
“…However, these particular 16S rRNA bases are paired in the 30S subunits, making the MazF-dependent cleavage very unlikely. It was later shown that indeed, MazF cleaves the rRNAs in their precursor states, before the 30S subunit biogenesis, and at multiple sites (Mets et al, 2017;Culviner and Laub, 2018). This is in agreement with structural data showing that MazF binds to single-stranded RNA (ssRNA) and interacts with the bases (Simanshu et al, 2013;Zorzini et al, 2016).…”
Section: Mazf Toxinssupporting
confidence: 77%
“…Most of the MazF toxins prefer U upstream of cleavage (at position −1) and AC downstream of cleavage (at positions +1 and +2, respectively) with less stringency outside of the two to four main recognized bases (Figure 2). The E. coli MazF cleaves in the coding as well as untranslated regions of mRNAs, independent from the reading frame, and in rRNA precursors (Mets et al, 2017;Culviner and Laub, 2018;Mets et al, 2019). Slight changes in sequence specificity of different MazF enzymes from different bacteria, correspond well to their amino acid sequence similarity (Figure 2).…”
Section: Mazf Toxinsmentioning
confidence: 96%
See 1 more Smart Citation
“…Our results indicate that, although MazF does not significantly impact mature rRNA, it does have a major effect on rRNA precursors. One recent study of E. coli MazF had suggested that it may cleave precursor rRNAs (Mets et al, 2017) based on 5 0 -OH mapping that produced a peak in the 16S precursor and several peaks within structured regions of 16S and 23S rRNA. However, these experiments were conducted after MazF was expressed for 2 hr using the 5 0 -OH method, so whether these peaks indicate common products or rare but stable products is unclear.…”
Section: A Global Analysis Of Rna Cleavage By Mazf Reveals Its Specifmentioning
confidence: 99%
“…Promoting translation through MazF cleavage of leader regions was proposed to be widespread in E. coli, with the MazF regulon suggested to include >300 transcripts (Sauert et al, 2016). Work by a different group also found that MazF triggered production of a 43-nt fragment corresponding to the 3 0 end of 16S rRNA but then provided evidence MazF could be cleaving rRNA precursors as well (Mets et al, 2017). However, that study did not formally separate or quantify MazF's effects on rRNA precursors and mature rRNA.…”
Section: Introductionmentioning
confidence: 99%